Вы находитесь на странице: 1из 29

# Generalizations of the Classical Tannery's Theorem

John Gill
2010

## ABSTRACT: Inner Composition of analytic functions ( f1  f 2  f n (z) ) and Outer

Composition of analytic functions ( f n  f n −1  f1 (z) ) are variations on simple iteration,
and their convergence behaviors may reflect that of simple iteration of a contraction
mapping described by Henrici . Investigations of the more complicated structures
f1,n  f 2,n  f n,n (z) and f n,n  f n −1,n  f1,n (z) lead to extensions of the classical
Tannery's Theorem . A variety of examples and original minor theorems related to the
topic are presented. The paper is devised in the spirit of elementary classical analysis and
much is accessible to serious undergraduate majors; there is little reference to modern, or
"soft" analysis. [AMS Subject Classifications 40A30, primary,30E99, secondary. October 2010]

1. Preliminaries:

Tannery's Theorem  provides sufficient conditions on the series-like expression S(n)
= a1 (n) + a 2 (n) +  + a n (n) that it converge to the limit of the series a1 + a 2 +  , when
lim a k (n) = a k for each k. In fact, the original theorem provided this result for a more
n →∞

## general series-like expansion , S(p,n) = a1 (n) + a 2 (n) +  + a p (n) , where it is

understood that p tends steadily to infinity with n. In this and subsequent notes p will be
taken to be n.

_______________________________________________

Tannery's Theorem (series): Suppose that S(n) = a1 (n) + a 2 (n) +  + a n (n) , where
lim a k (n) = a k for each k. Furthermore, assume a k (n) ≤ M k with
n →∞
∑M k <∞.
Then lim S(n) = a1 + a 2 +  , convergent.
n →∞
________________________________________________

## Proof: (sketch) Write

a1 (n) + a 2 (n) +  + a n (n) − ( a1 + a 2 +  + a n )
p n n
,
≤ ∑ a k (n) − a k + ∑ a k (n) + ∑ ak
k=1 k = p +1 k = p +1

Etc. ||
Setting f k,n (z) = a k (n) + z , then one may write

S(n) = f1,n  f 2,n  f n,n (0) , or S(n) = f n,n  f n −1,n  f1,n (0) .

## The classical Tannery theory can easily be extended to infinite products:

____________________________________________________
n
Tannery's Theorem (products): Suppose that P(n) = ∏ (1 + a k (n)) . If
k =1

lim a k (n) = a k , and a k (n) ≤ M k with
n →∞
∑M k < ∞ , then lim P(n) = ∏ (1 + a k ) .
n →∞
k =1
_____________________________________________________

(n) ) = e∑
ln(1+ a k (n )) 3 1
Proof: (sketch) ∏ (1 + a k , ln(1+z) <
2
z if z <
2
Apply Tannery's Theorem for series . . . ||

However, the original theorem is less adaptable to more exotic expansions like continued
fractions:
a (n) a 2 (n) a n (n)
C(n) = 1  ,
1+ 1+ 1
which can be expressed as

a k (n)
C(n) = f1,n  f 2,n  f n,n (0) , with f k,n (z) = .
1+ z

## Nevertheless, a unifying principle applicable to a variety of expansions exists if we

restrict our attention to scenarios in which all functions f n (z) and f k,n map simply-
connected domain into a compact subset of itself. A simple example of the kinds of
possible extensions of classical Tannery's Theorem is the following (theory developed
later in this paper):

a1 a 2 an 1
Example: The continued fraction → λ as n → ∞ , if a k <
1 + 1 ++ 1 4
1
Suppose lim a k (n) = a k for each k ≤ n and a k (n) < for all such terms .
n →∞ 4
a1 (n) a 2 (n) a n (n)
Then → λ as n → ∞
1 + 1 +  + 1
A continuous analog of the Tannery Theorem is the following:
__________________________________________________________

## Tannery's Theorem (continuous): [Let {f n (x)} be a sequence of functions

continuous on R]. Suppose lim f n (x) = g(x) uniformly in any fixed interval, and there
n →∞

exists a positive function M(x) where f n (x) ≤ M(x) and ∫ M(x)dx
a
converges.
n ∞
Then lim ∫ f n (x)dx = ∫ g(x)dx .
n →∞
a a

_________________________________________________________
_________________________________________________________

## The classical Tannery's Theorem provides the following result:

lim ( a1 (n) + a 2 (n) +  + a n (n) ) = lim a1 (n) + lim a 2 (n) +  + lim a n (n)
n →∞ n →∞ n →∞ n →∞

## The generalizations described here take the forms:

lim t1,n  t 2,n  t n.n (z) = lim t1,n  lim t 2,n  lim t n,n (z)
n →∞ n →∞ n →∞ n →∞

or
lim t n,n  t n-1,n  t1,n (z) = lim t n,n  lim t n −1,n  lim t1,n (z)
n →∞ n →∞ n →∞ n →∞

Additional theory addresses scenarios in which the distribution of limits shown above
does not occur (e.g., the Riemann Integral) . . . making mathematical life a bit more
interesting.

. . .
2. Extending Tannery's Theorem to Inner Composition with Contractions

## By contractions is meant the following domain contractions:

__________________________________________________________

Theorem (Henrici , 1974). Let f be analytic in a simply-connected region S and continuous on the
closure S' of S. Suppose f(S') is a bounded set contained in S. Then f n (z) = f  f  f (z) → α , the
attractive fixed point of f in S, for all z in S'.
___________________________________________________________
This result can be extended to forward iteration (or inner composition) involving a
sequence of functions:
___________________________________________________

## Theorem 2.1:(Lorentzen, ,1990 ) Let {f n } be a sequence of functions analytic on a

simply-connected domain D. Suppose there exists a compact set Ω ⊂ D such that for
each n, f n (D) ⊂ Ω . Then Fn (z) = f1  f 2  f n (z) converges uniformly in D to a
constant function F(z) = λ .
___________________________________________________________

(Note: This result is sometimes called the Lorentzen-Gill Theorem since the second author obtained the
result in a specific case in previous papers , )

## The concept underlying Tannery's Theorem extends easily to this setting:

______________________________________________________________

## Theorem 2.2: (Gill, ,1992) Let {f k,n }, 1 ≤ k ≤ n be a family of functions analytic on

a simply-connected domain D. Suppose there exists a compact set Ω ⊂ D such that for
each k and n, f k,n (D) ⊂ Ω and, in addition, lim f k,n (z) = f k (z) uniformly on D for each k.
n →∞

## Fn,n (z) → λ , a constant function , as n → ∞ , uniformly on D.

____________________________________________________________

Comment: The condition lim f k,n (z) = f k (z) , if discarded, allows the possibility of
n →∞
divergence by oscillation: viz.,

## f1,n (z) = {−.5.5 ifif nn isis odd

even
, otherwise f k,n
z
(z) ≡ , on S = ( z < 1) .
2

Proof: Theorem 2.1 defines λ . Write Zp,n = f p +1,n  f p + 2,n  f n,n (z) . Then
Fn,n (z) − λ = Fp,n (Z p,n ) − λ

## ≤ Fp,n (Z p,n ) − Fp (Zp,n ) + Fp (Z p,n ) − λ

ε
For the second term in the inequality, choose and fix p sufficiently large that Fp (z) − λ < for all z in
2
ε
D. For the first term, choose n sufficiently large to insure Fp,n (z) − Fp (z) <
for all z in D. This is true
2
since a finite composition of functions of the type described above, converging uniformly on D, will also
converge uniformly on D. ||
A Tannery Transformation: An existing compositional structure Fn (z) = f1  f 2  f n (z) may be
transformed using these ideas:

## Corollary: Let {f n } be a sequence of functions analytic on a simply-connected domain

D. Suppose there exists a compact set Ω ⊂ D such that for each n, f n (D) ⊂ Ω . Now
suppose there exists a sequence of functions analytic on D and depending upon both k
and n, {t k,n }, such that t k,n (D) ⊂ Ω and lim t k,n (z) = z uniformly on D, for each k.
n →∞
Then
Tn (z) = f1  t1,n  f 2  t 2,n  f n  t n,n (z) → λ ,
.
where Fn (z) = f1  f 2  f n (z) → λ .

Proof: Set g k,n (z) = f k (t k,n (z)) and apply the theorem. ||

## Example: fixed-point continued fractions

α1 (α1 + 1) α 2 (α 2 + 1) α (α + 1)
Cn (ω) = ... n n
1 + 1 + 1 + ω

1 1
converges under the following stipulations: αn < , ω<
. The { α n } are the
5 2
α (α + 1)
attractive fixed points of the linear fractional transformations t k (ω) = k k .
1+ ω
Thus, one may write Cn (ω) = t1  t 2  t n (ω) . (If α n ≡ α , then lim Cn (ω) = α ).
n →∞

## α1 (n)(α1 (n) + 1) α 2 (n)(α 2 (n) + 1) α (n)(α n (n) + 1)

Writing Cn,n (ω) = ... n , where
1 + 1 + 1 + ω

lim α k (n) = α k for each k, we have lim Cn,n (ω) = lim Cn (ω) .
n →∞ n →∞ n →∞

1  1  1  
Example: Nested logarithms Ln  2 + Ln  3 + Ln ( 4 + )  
2  3  4  
1
Here, t k (z) = Ln(k + 1 + z) , z < 1 ⇒ t k (z) ≤ ρ < 1 . Thus,
k +1
t1  t n (z) → .438699 . Similarly,
1  1 
Ln  2 ⋅ a1 (n) + Ln ( 3 ⋅ a 2 (n) + )  , where 1 ≤ a k (n) → 1 , converges to the same
2  3 
limit. The obvious choice for an initial value of z is 0.

## Example: Iteration of Functions defined by Infinite Integrals

∞ n
t k (z) = ∫ ϕk (t, z)dt or t k,n (z) = ∫ ϕk (t, z)dt
0 0
n
For instance: t k,n (z) = ∫ e − t(k +1+ε+ z) dt , z < 1. Giving rise to a complicated expansion
0
that converges to the limit of the continued fraction:

1
t1,n  t n,n (z) →
1
2+ε+
1
3+ε+
4+ε

. . .
Extending Tannery's Theorem to Inner Compositions without Contractions

____________________________________________________

## Theorem 2.3: (Gill, 2011) Consider sequences of polynomials converging to entire

functions: f k,n (z) = z + a 2,k z 2 + a 3,k z3 +  + a n,k z n → f k (z) as n → ∞ for k=1,2,3, . . .
Set φk ,n (z) = z + a 2,k (n)z 2 + a 3,k (n)z 3 +  + a n,k (n)z n where lim a j,k (n) = a j,k ∀k,j ,
n →∞

a j,k (n) < ρkj−1 for all n , and ∑ρ
k =1
k < ∞ . Next, set Fk (z) = f1  f 2  f k (z) , where

F(z) = lim Fk (z) , and Φ p,n (z) = φ1,n  φ2,n  φp,n (z) , Zp,n = φp +1,n  φp + 2,n  φn ,n (z) .
k →∞
Then
lim Φ n,n (z) = F(z) .
n →∞

_______________________________________________________

z R
Outline of Proof: Consider z ≤ R . Then, φk,n (z) ≤ ≤ , which may
1 − ρk z 1 − ρk R
be repeated to give Zp,n ≤ R 0 = 2R . The original Tannery's Theorem shows that
φk ,n (z) → f k (z) uniformly on ( z ≤ R 0 ) = S. As in Kojima's Theorem ,
2
ρp z
φp,n (z) − z ≤ , which may be used to prove that
1 − ρp z

Zp,n − z ≤ 2R ⋅ 2
0 ∑ρ
k = p +1
k → 0 as p → ∞ .

## Φ n,n (z) − F(z) ≤ Φ p,n (Zp,n ) − Fp (Zp,n )

Writing + Fp (Zp,n ) − F(Zp,n )
+ F(Zp,n ) − F(Z)
ε
choose p so large that each of the last two expressions are less than (functions
3
ε
converge uniformly on S ) . Then choose n so large that the first is less than .
3
ε ε ε
Therefore Φ n,n (z) − F(z) < + + = ε ||
3 3 3

___________________________________________________________

## Theorem 2.4 : Let S be a simply-connected domain and {t k,n } , k ≤ n , a sequence of

functions analytic in S where t k,n (S) ⊂ S and t k,n (z) → t k (z) for each k Suppose that
(a) t k,n (z) − t k (z) < ε k (n) → 0 , as n → ∞ for all z in S, and
(b) t k (z1 ) − t k (z 2 ) < ρk z1 − z 2 , ∀z1 ,z 2 in S .
n k −1 
Then t1,n  t 2,n  t n ,n (z) − t1  t 2  t n (z) < ∑  ∏ ρ j ε k (n)
k =1  j= 0 
___________________________________________________________

Proof: Set Φ p,n = t p,n  t p +1,n  t n,n (z) and Ψ p,n = t p  t p +1  t n (z)

Then
Φ1,n − Ψ1,n ≤ t1,n (Φ 2,n ) − t1 (Φ 2,n ) + t1 (Φ 2,n ) − t1 (Ψ 2,n )

## < ε1 (n) + ρ1  t 2,n (Φ 3,n ) − t 2 (Φ 3,n ) + t 2 (Φ 3,n ) − t 2 (Ψ 3,n ) 

i
i
i
n  k-1 
< ∑  ∏ ρ j ε k (n)
k=1  j=0 

Since the values of { ρk } are not necessarily less than one, { Ψ1,n (z) } might diverge and
{ Φ1,n (z) } simply track that sequence, assuming t k,n → t k rapidly enough. ||

## C1 (n)z C2 (n)z C n (n)z

1 + 1 ++ 1

C k (n)z
Here t k,n (w) = , with w < r < 1 , z < R , and C k (n) < C .
1+ w

CR r(1-r)
t k,n (w) < with R < insures t k,n (w) < r when w < r .
1− r C

R R
From (a) of Theorem 2.4 , t k,n (w) − t k (w) < Ck (n) − Ck < σk (n) , and
1− r 1− r

CR
(b) t k,n (w1 ) − t k ,n (w 2 ) < = ρ . Therefore
(1-r)2

n
R
t1,n  t 2,n  t n,n (z) − t1  t 2  t n (z) <
1-r
∑ρ
k =1
k −1
σk (n) .

1 1 k
To illustrate, let r = , R= , C=1 , σ k (n)= 3 . Hence ρ k ≡ 1 .
2 4 n

## This gives, after a few calculations,

C1 (n)z C2 (n)z C n (n)z C1z C2 z Cn z 1  1
− < 1 +  → 0 , so that
1 + 1 ++ 1 1 + 1 ++ 1 4n  n 

## C1 (n)z C 2 (n)z Cn (n)z

Fn (z) = → F(z) , analytic in z < R .
1 + 1 +  + 1

## Example: Variation on Continuous Analogue of Tannery's Theorem

k k
Employing Theorem 2.4, set t k,n (z) = ∫ f (x, n)dx + z ,
k −1
and t k (z) = ∫ g(x)dx + z ,
k −1

with lim F(x, n) = g(x) . Then t k,n (z) − t k (z) ≤ Max f (x, n) − g(x) = ε k (n)
n →∞ k −1≤ x ≤ k

n n n

## ∫ f (x, n)dx − ∫ g(x)dx ≤ ∑ε

k =1
k (n)
0 o

If the sum tends to zero, the first integral grows closer to the second, even if the second
integral diverges.

n
1
Example: ∫ sin(x + σ(n))dx ,
0
where , e.g., σ(n) <
n3
, approximates to any required
n
degree of accuracy the divergent integral ∫ sin(x)dx
0

## all entries are positive real numbers. When does

R n,n → lim σ1 + σ 2 +  + σ n ?
n →∞

## σk (n), σ k ≥ M(k) > 0, and σk (n) − σk < δk (n) → 0 .

Then conditions (a) and (b) assume the forms
σk (n) − σ k 1 δ (n)
(a) t k,n (z) − t k (z) ≤ ≤ σk (n) − σk < k = ε k (n) ,
σk (n) + σk 2M(k) 2M(k)
1
(b) t k (z1 ) − t k (z 2 ) ≤ z1 − z 2 = ρk z1 − z 2
2M(k)
Hence
n k
1 δ k (n)
t1,n  t n,n (0) − t1  t n (0) < ∑∏ M( j) ⋅
k =1 j=1 2k
.

1 1 1
Example: 1 + + 2 + + 3 + + − 1+ 2 + 3 + → 0 .
n n n

We find that
1 n 1
t1,n  t n,n (0) − t1  t n (0) < ∑ k
n k =1 2 k!
→ 0.

## Example: (trivial), from Example 4 above: Definite Integrals :

n
1 k
Given φ ∈ C[0,1] and a k (n) − φ( ) < ε k (n) , where
n n
∑ε
k =1
k (n) → 0 . Then
n 1

∑ a k (n) →
k =1
∫ φ(t) dt .
0

1
1 k k2 n
k2 + n 1
Example: φ(t) = t 2
⇒ φ( ) = 3 , hence
n n n

k =1 n3
→ ∫ t dt =
2

3
0

## Example: Exponential Expansion

z 1 kz n
Tn ,n (z) = t1,n  t 2,n  t n,n (z) , where t k,n (z) = + e , n ≥ 2 , z ≤ 1.
n 6
5
Hence t k,n (z) < 1 , ρk ≡ 0 , and ε1 (n) < →0 .
3n
1 1
Thus t k,n (z) → t k (z) ≡ and Theorem 7 ⇒ Tn,n (z) → .
6 6

. . .

## Related to Theorem 2.4 is the following result:

__________________________________________________________________

## Theorem 2.5 (Gill 2011) Consider the nested sets S = ( z ≤ R ) , S1 = ( z ≤ R1 ) ,

Cρ 2Cρ
S2 = ( z ≤ R 2 ) where R 1 = R + and R 2 = R + . Let {f k,n } be a family of
1− ρ 1− ρ
functions analytic on S2 and 0 ≤ ρ < 1 , where:

(1) f k,n (z) − z ≤ Cρk on S2 and (2) f k,n (z) → f k (z) as n → ∞ , uniformly on S2 .

Set Zp,n = f p +1,n  f p + 2,n  f n,n (z) , Fp,n (z) = f1,n  f 2,n  f p,n (z) , and
Fn (z) = f1  f 2  f n (z) . Then there exists a function F(z) analytic on S1 such that

## Fn (z) → F(z) uniformly on S1 and Fn,n (z) → F(z) uniformly on S.

_____________________________________________________________________

Sketch of proof: Theorem 2.6  shows that Fn (z) → F(z) uniformly on S1 .
Next, for z ∈ S ,

## f n,n (z) ≤ z + Cρn ≤ R + Cρn

f n-1,n  f n,n (z) ≤ R + Cρn + Cρn −1
.
.
.
Zp,n ≤ R1 I.e., Zp,n ∈ S1 .

Now write Fn,n (z) − F(z) ≤ Fp,n ( Z p,n ) − Fp ( Z p,n ) + Fp ( Zp,n ) − F(z)
ε
Fix p so large that the second term on the right is < . If n is sufficiently large
2
ε
the first term on the right side is < . Hence, for z ∈ S , Fn,n (z) → F(z) on S. ||
2

## 3. Extending Tannery's Theorem to Outer Composition with Contractions

_____________________________________________________________

Theorem 3.1: (Henrici , 1974). Let f be analytic in a simply-connected region S and continuous on
the closure S' of S. Suppose f(S') is a bounded set contained in S. Then f n (z) = f  f  f (z) → α , the
attractive fixed point of f in S, for all z in S'.
______________________________________________________________

## This fundamental result for contraction mappings can be extended to an infinite

composition of functions arranged as backward iteration (or outer composition) :
_______________________________________________________________
Theorem 3.2 : [Gill, ,1991) Let {g n } be a sequence of functions analytic on a simply-connected
domain D and continuous on the closure of D. Suppose there exists a compact set Ω ⊂ D such that
g n (D) ⊂ Ω for all n. Define G n (z) = g n  g n −1  g1 (z) . Then G n (z) → α uniformly on the closure
of D if and only if the sequence of fixed points {α n } of the {g n } in Ω converge to the number α .
________________________________________________________________
comment: The existence of the {α n } is guaranteed by Theorem 1. Note the simple counter-example
g n (z) = −.5 for n odd and g n (z) = .5 for n even, in the unit disk (|z|<1). It is not essential that g n → g ,
although that is usually the case. If g n → g , then α n → α .

ez ez ez
Example: let G(z) = 4 8 12 … , where z ≤ 1 . We solve the continued fraction
3+ z + 3+ z + 3+ z +
e z 4n
equation G(α) = α in the following way: Set t n (ξ) = ; let g n (z) = t1  t 2  t n (0) .
3+ z + ξ
Now calculate G n (z) = g n  g n −1  g1 (z) , starting with z = 1. One obtains α = .087118118
to ten decimal places after ten iterations .

Next, consider a sequence of functions {g k,n } dependent upon both k and n and defined on a suitable
domain D. Define G p,n (z) = g p,n  g p −1,n  g1,n (z) , with p ≤ n .
_______________________________________________________

## Theorem 3.3: Suppose {g k,n }, with k ≤ n , is a family of functions analytic on a simply-connected

domain D and continuous on its closure, with g k,n (D) ⊂ Ω , a compact subset of D, for all k and n.
Then
G n ,n (z) = g n,n  g n −1,n  g1,n (z) → α uniformly on the closure of D
if and only if
the sequence of fixed points {α k,n } of {g k,n } converge* to α .
___________________________________________________________________
Comments: When lim g k,n (z) = g k (z) , for each value of k, both sequences converge to the limit
n →∞

## Proof: The proof (of sufficiency) is similar to that of theorem 3.2.

z−α
Set D = (|z|<1). Let Φ(z) : = . Then Φ : D → D is analytic there, with Φ(α) = 0 and
1 − αz
Φ −1 (0) = α . Set q k,n (z) = Φ  g k,n  Φ −1 (z) .

## Lemma : q k,n (0) → 0 as both k, n → ∞ .

Proof of Lemma: This result will follow if g k,n (α) → α . Write

(1) g k ,n ( α ) − α ≤ g k ,n ( α ) − g k ,n ( α k ,n ) + α k ,n − α

For ε > 0 , choose K and N such that k>K and n>N imply each term of the right side of (1)
ε
is less than . This is possible for the first term because the {g k,n } are uniformly bounded on D, thus
2
equicontinuous there. Hence q k,n (0) → 0 as k, n → ∞ .

Now, the existence of the compact set Ω implies g k,n (z) ≤ µ < 1 for all z in D. Thus
(2) Sup(Sup q k,n (z) = ρ < 1 exists.
k,n z <1

Since q k,n (0) → 0 as k, n → ∞ , there exists a sequence {ε k,n } such that 0 ≤ ε k,n → 0 as k, n → ∞ ,
and q k,n (0) ≤ ε K,N for all k>K and n>N. (E.g., set ε K,N = Sup q k,n (0) )
k > K,n > N

q k,n (z)
Set H k ,n (z) = . Then H k,n (z) < 1 for all |z|<1. An application of Schwartz's Lemma 
ρ
gives
H k,n (0) + z
H k,n (z) ≤ ≤ H k,n (0) + z .
1 + H k,n (0) ⋅ z
Therefore

## (3) q k,n (z) ≤ q k,n (0) + z ρ .

Next, set Q k,n (z) = q k,n  q k −1,n  q1,n (z) for all k and n. Then from (2),

## (4) Q k ,n (z) < ρ < 1 for all k and n.

Writing p = n + m , begin an inductive procedure with an arbitrary but large value of n, with the goal of
proving that Q p,p (z) → 0 as p tends to infinity. Employing backward recursion, using (3) and (4):

Q n + m,n + m (z) = q n + m,n + m (Q n + m −1,n + m (z)) ≤ q n + m,n + m (0) + ρ Q n + m −1,n + m (z) < ε n,n + ρ Q n + m −1,n + m (z)
≤ ε n,n + ρ{ q n + m −1,n + m (0) + ρ Q n + m − 2,n + m (z) }
< ε n,n + ρε n,n + ρ2 Q n + m − 2,n + m (z)
≤ ε n,n (1 + ρ) + ρ2 { q n + m − 2,n + m (0) + ρ Q n + m −3,n + m (z) }
< ε n,n (1 + ρ) + ε n ,n ρ2 + ρ3 Q n + m −3,n + m (z)
≤ ε n,n (1 + ρ + ρ2 ) + ρ3{ q n + m −3,n + m (0) + ρ Q n + m − 4,n + m (z) }
< ε n,n (1 + ρ + ρ2 + ρ3 ) + ρ4 Q n + m − 4,n + m (z)
.
.
.
ε n,n ε n,n
< + ρm −1 Q n +1,n + m (z) < + ρm
1− ρ 1− ρ

Thus, if n and m are large enough (p is large enough) both terms of the last expression can be made as
small as one wishes. Hence Q p,p (z) → 0 as p tends to infinity. It follows immediately that
G n ,n (z) → α for all z in D. It is a simple matter to extend these results to more general simply-
connected domains, D, by using appropriate Riemann Mapping Functions. ||

## Example: The modified fixed-point continued fraction seen before

α1 (α1 + 1) α 2 (α 2 + 1) α (α + 1)
Cn (ω) = ... n n
1 + 1 + 1 + ω

## can be reconfigured to give a modified reverse fixed-point continued fraction:

α n (α n + 1) α n −1 (α n −1 + 1) α (α + 1)
G n (ω) = ... 1 1
1 + 1 + 1 + ω
1 1
convergent when α n < , ω < , and lim α n = α . The { α n } are the attractive
5 2 n →∞

α (α + 1)
fixed points of the linear fractional transformations t k (ω) = k k .
1+ ω
Thus, one may write G n (ω) = t n  t n −1  t1 (ω) → α , as n → ∞ .
α n (n)(α n (n) + 1) α n −1 (n)(α n −1 (n) + 1) α (n)(α1 (n) + 1)
Setting G n ,n (ω) = ... 1 ,
1 + 1 + 1 + ω
where lim α k (n) = α , we have
k,n →∞

n →∞ n →∞

## The following result extends the scope of Theorem 3.3 somewhat:

__________________________________________________________________

Theorem 3.3a: Suppose {g k,n (ζ, z)} , with k ≤ n , is a sequence of functions analytic with respect to z
on a simply-connected domain, D, for each ζ ∈ S , a second simply-connected domain, with
g k,n (S, D) ⊂ Ω , a compact subset of D, for all k and n. Let the sequence of fixed points {α k,n (ζ )} of
{g k,n } converge to α(ζ ) uniformly on S. (I.e., α k,n → α as both k and n → ∞ , with k ≤ n ). Then
G n ,n (z) = g n,n  g n −1,n  g1,n (z) → α(ζ ) uniformly on S × D
___________________________________________________________________

. . .
4. Extending Results for Outer Composition without Contractions
___________________________________________________________

## Theorem 4.1: Let {g n } be a sequence of functions analytic on a simply-connected

domain D. Let g n (D) ⊂ D for all n. Suppose there exists a sequence of fixed points
{α n } of the {g n } in D converging to a number α , and
(1) g k (z) − α k ≤ ρk z − α k , 0 ≤ ρk < 1 and (2) α-α k < ε k → 0

## then , setting H n ,n + p (z) = g n + p  g n + p −1  g n (z) ,

n +p n+p-1 n+p
H n,n + p (z) − α ≤ z − α ⋅ ∏ ρk + 2 ∑ ε k ⋅ ∏ ρ j + 2ε n + p
k =n k=n j= k +1
n −1
 n
n

In particular G n (z) − α = H1,n (z) − α = z − α ∏ ρk + 2∑  ε k ∏ ρ j  + 2ε n
1 1  k +1 
_____________________________________________________________

## Proof: The repeated application of the inequality

g n (z) − α ≤ g n (z) − α n + α − α n and use of the fact that ρk < 1 are sufficient. ||

1 1
Comment: The simple example in which ρk = 1 − and ε k = 2 for D=(|z|<1) lies
k k
outside the context of Theorem 3.2 , and yields, after simplification,

1 2 1 1 1  2
G n (z) − α < z−α +  + + + + → 0 as n → ∞
n +1 n +1  2 3 n − 1 n 2

α k (α k + 1)
Example: Let g k (z) = , with D = {z:|z|< 12 } .
1+ z
Set
2 −1 1 1
αk = − . Then α -α k = and g k (D) ⊆ D. And
2 k+4 k+4

αk 1 1
ρk = < , g k (z) → g(z) = 4 . Thus, after simplification,
1+ z 2 1+ z

1  1 1 1  2
G n (z) − α < z −α + 2 + 2 +  n −1  + = E(n)
 2 ( n + 3) 2 (n + 2)
n
2 2 (5)  n + 4

Applying the original Tannery's Theorem to the series component shows E(n) tends to
zero as n becomes infinite.
Extending the result above to Tannery continuous compositions, we have
_____________________________________________________________

## Theorem 4.2 : Let {g n } be a sequence of functions analytic on a simply-connected

domain D. Let g n (D) ⊂ D for all n. Define G n (z) = g n  g n −1  g1 (z) . Suppose there
exists a sequence of fixed points {α n } of the {g n } in D converging to a number α , and
suppose {g k,n }, with k ≤ n , is a sequence of functions analytic on a simply-connected
domain D, with g k,n (D) ⊂ D , and G p,n (z) = g p,n  g p −1,n  g1,n (z) . Assume further
(1) g k,n (z) − g k (z) < σk (n) → 0 as n → ∞
(2) g n (ζ1 ) − g n (ζ 2 ) < ρn ζ1 − ζ 2 , 0 ≤ ρn < 1
(3) α − αn < εn → 0
n n-1 n
G n,n (z) − α ≤ z − α ⋅ ∏ ρk + ∑ ηk (n) ⋅ ∏ ρ j + ηn (n) ,
Then k =1 k=1 j= k +1
where ηk (n) = σk (n) + 2ε k
___________________________________________________________

## It is easily seen that

n −1  n 
(4) G n,n (z) − G n (z) < σn (n) + ∑  ∏ ρ j σk (n)
k =1  j= k +1 
And, from the previous theorem,
n n-1 n
G n (z) − α ≤ z − α ⋅ ∏ ρk + 2∑ ε k ⋅ ∏ ρ j + 2ε n , so that
k =1 k=1 j= k +1

n n-1 n
G n,n (z) − α ≤ z − α ⋅ ∏ ρk +
k =1
∑ η (n) ⋅ ∏ ρ
k=1
k
j= k +1
j + ηn (n) , ηk (n) = σ k (n) + 2ε k ||

kπ kπ k
Example: Let g k (z) = sin( + z) , g k,n (z) = sin( + 3 + z) , -1 ≤ z ≤ 1
2 2 n
k k
Then σk (n) = and ρk ≡ 1 σk (n) = 3 and ρk ≡ 1 . From (4) above,
n3 n

nπ n (n − 1)π n − 1 nπ (n − 1)π 1 1
sin( + 4 + sin( + 4 + ) − sin( + sin( + ) < (1 + ) → 0
2 n 2 n 2 2 2n n

## Although neither sequence converges.

Another result:
_________________________________________________

Theorem 2.7: (Gill,  2011) Let {g n } be a sequence of complex functions defined

on S0 =(|z| ≤ R 0 ) . Suppose there exists a sequence {ρn } such that ∑ρ
k=1
n < ∞ and

g n (z) − z < Cρn if z ≤ R 0 . Set σ = C∑ ρk and R 0 = R+σ . Then, for every
1

## z ∈ S = ( z ≤ R ) , G n (z) = g n  g n −1  g1 (z) → G(z) , uniformly on compact subsets

of S .
_________________________________________________

## Which can be extended to another Tannery result:

________________________________________________________

Theorem 2.8: (Gill 2011) Suppose the functions {g k,n } are defined on S0 = (| z |≤ R 0 ) ,

{ρn } are positive, σ = C∑ ρk converges, and S = (| z |≤ R) , R + σ = R 0 . Assume
k =1

(1) g k,n (z) → g k (z) uniformly on S0 and (2) g k,n (z) − z ≤ Cρk there as well.
Then for z ∈ S ,
lim G n ,n (z) = G(z) = lim G n (z) .
n →∞ n →∞

_________________________________________________________

Outline of Proof: Theorem 2.7 shows G n = G n (z) = g n  g n −1  g1 (z) → G(z) and
(2) may be used repeatedly to show g p,n  g p −1,n  g1,n (z) ≤ R 0 .
Now, write G n,n − G ≤ G n,n − G n + G n − G , in which
n n
G n,n − G n ≤ ∑
k = p +1
G k,n − G k −1,n + ∑
k = p +1
G k − G k −1 + G p,n − G p

≤ 2∑ ρk + g p,n (G p −1,n ) − g p (G p −1,n ) + g p (G p −1,n ) − g p (G p −1 )
k =p

ε ε ε ε ε
< 2⋅ + + =
12 6 6 2
if p is chosen large enough to insure ∑ρ
k =p
k <
12
,

ε
and then n is large enough to guarantee each of the last two expressions is < .
6
( {g k,n } and {g k } equicontinuous on S0 , and (1) above)
ε
Thus, for large n, Gn − G < and the proof is complete. ||
2

. . .
5. Tannery Theory Potpourri . . . Trivia and Such

Comment : Consider Tn ,n (z) = t1,n  t 2,n  t n,n (z) where each function is of the form
t k,n (z) = a k (n) + z and lim a k (n) = a k . Then
n →∞

## Tn ,n (0) = a1 (n) + a 2 (n) +  + a n (n) .

Tannery's original theorem covered this sort of thing, using uniform convergence
properties:
lim[a1 (n) + a 2 (n) +  + a n (n)] = a1 + a 2 + 
n →∞

## Several examples where TT may or may not apply:

n
In each instance, a k (n) → a k ≡ 0 as n → ∞ . Does lim ∑ a k (n) = 0 ?
n →∞
k =1

n
k
Example 1: a k (n) = ⇒ lim Tn,n (0) = lim ∑ a k (n) = ∞
n n →∞ n →∞
k =1

n
k 1
Example 2: a k (n) =
n 2
⇒ lim
n →∞
Tn,n (0) = lim
n →∞

k =1
a k (n) =
2

n
k
Example 3: a k (n) =
n3
⇒ lim
n →∞
Tn ,n (0) = lim
n →∞

k =1
a k (n) = a1 + a 2 +  = 0 + 0 +  = 0

1
1 k n
Example 4: a k (n) = f   , f ∈ C[0,1] ⇒ lim Tn,n (0) = lim ∑ a k (n) = ∫ f (x)dx
n n n →∞ n →∞
k =1 0
Simple observations arising from the preceding examples . . .

___________________________________________________________

Theorem 5.1 : Suppose lim a k (n) ≡ 0 for S(n) = a1 (n) + a 2 (n) +  + a n (n) . Then
n →∞

ρ
(a) a k (n) ≥ ⇒ S(n) ≥ ρ
n
1
(b) a k (n) ≤ 1+α , α >0 ⇒ S(n) → 0
n
m
(c) a k +1 (n) ≥ ρ ⋅ a k (n) , ρ>1 , a1 (n) ≥ ⇒ S(n) ≥ m>0
ρn −1
(d) a k +1 (n) ≤ ρ ⋅ a k (n) , ρ < 1 ⇒ S(n) → 0
___________________________________________________________

## In more general settings:

{
n
Example 5: a k (n) = 0 if k<n shows that lim Tn ,n (0) = lim ∑ a k (n) may exist in the
1 if k=n n →∞ n →∞
k =1

## absence of the condition a n (n) → 0 .

{
Example 6: a k (n) = 1 if k<n shows that a n (n) → 0 does not imply
0 if k=n
n
lim Tn ,n (0) = lim ∑ a k (n) exists (in a finite sense).
n →∞ n →∞
k =1

## S(n) = a1 (n) + a 2 (n) +  + a n (n) , with

λ (k)
a k (n) − a k < ε k,n ≤ , where λ(k) is a linear function of k and β > 2 .

## Then lim S(n) = a1 + a 2 +  , provided

n →∞
∑a k converges.
Tighter conditions are possible, but this simple example shows that the original Tannery's
Theorem for series has more latitude.

## Alternating series Sn = a1 − a 2 + a 3 −  + (−1) n +1 a n require only that

a n > a n +1 and lim a n = 0 for convergence, so it would seem reasonable that a Tannery
n →∞

Series, S(n) = a1 (n) − a 2 (n) +  + (−1) n +1 a n (n) , in order to converge to the alternating
series, should exhibit a fairly rapid convergence of individual terms to those of the series.
Theorem 2.4 is applicable ( t k,n (z) = a k (n) + z ) in that
n
a k (n) − a k < ε k (n) with ∑ε
1
k (n) → 0 is sufficient to insure the convergence of the
n
alternating Tannery Series: S(n) − Sn < ∑ ε k (n) → 0
1

n2 2n 2 3n 2 n +1 n ⋅ n2
Example: S(n) = − + −  + (−1) . Here the
1 + n 2 1 + 4n 2 1 + 9n 2 1+ n2 ⋅ n2
1 1 1
corresponding alternating series is Sn = 1 − + −  + (−1) n +1
2 3 n
1 1
We find that a k (n) − a k < 2 so that S(n) - Sn < → 0.
n n

## An Integral Test for Tannery Series

The following result is an analogue of the familiar Integral Test for series. It doesn't
provide a spectacular new perspective on the subject . . . it's merely a curiosity that could
probably be improved:

_______________________________________________________

Theorem 5.3 : Let S(n) = a1 (n) + a 2 (n) +  + a n (n) , and suppose that there exists a
non-negative, bounded and differentiable function f(x,t) , defined for x ≥ 1 and t ≥ x ,
with f (k, n) = a k (n) , f t (x, t) > 0 and f x (x, t) < 0 , f (1, n) ≤ M . Then
n
lim S(n) exists if and only if lim ∫ f (x, n)dx exists
n →∞ n →∞
1
_________________________________________________________

n n

## ∫ f (x, n)dx + a n (n) ≤ S(n) ≤

1
∫ f (x, n)dx + a (n)
1
1

n
The hypotheses imply S(n) and ∫ f (x, n)dx
1
are monotonic increasing. If S(n)

## converges, a n (n) tends to zero. . . ||

Two simple examples illustrate the theorem:

Example:
n n n n 1 1 π2
S(n) = + +  + = (1 + +  + ) →
(n + 1)12 (n + 1)2 2 (n + 1)n 2 n + 1 4 n2 6

n
n 1 n π2
n + 1 ∫1 x 2
Here, dx + → 1+1=2 ≥
n +1 6

n
n n n 1
Example: S(n) = 2
+
n +1+1 n +1+ 2 2
+ +
n +1+ n2
(≥ ∑ 2+k
k=1
→ ∞)

n
n n  n 1 
Here, ∫ n +1+ x
1
2
dx =  Arc tan
n +1  n +1
− Arc tan  → ∞,
n +1 

n →∞

## Other Simple Results for Tannery Series

_______________________________________________________

Theorem 5.4 : Let S(n) = a1 (n) + a 2 (n) +  + a n (n) , and suppose there exists a non-
negative, bounded, and differentiable function f(x,t) defined for x ≥ 0 and t ≥ x , with
f (k, n) = a k (n) . Define φ(x) = f (x, x). Suppose
f x (x, t) ≥ 0 , f t (x, t) < 0 , and φ(x) → 0 as x → ∞. Also stipulate f (1, t) → 0 as t → ∞ .
Then
n
0 ← a1 (n) ≤ S(n) − ∫ f (x, n)dx
1
≤ a n (n) → 0 as n becomes infinite.

_________________________________________________________

## Proof: The easiest proof involves drawing a simple histogram. ||

x 1 −2k 1
Example: f (x, t) = 2
, then f x (x, t) = 2 > 0 , f t (x, t) = 3 < 0 and φ(x) = → 0.
t t t x
1 1  1 1
The theorem shows that 1 − 2  + - S(n) → 0, or lim S(n) = , as is easily
2 n  2 n →∞ 2
1
verified by evaluating S(n) directly: S(n) = 2 (1 + 2 + 3 +  + n ) .
n
Example: A slightly more sophisticated example is the following:

1 2 n
S(n) = 2 2
+ 2 2
+  + 2
1 +n 2 +n n + n2

x
Here f (x, t) = and the conditions of the theorem are satisfied for the relevant
x + t2
2

## values of the variables. Thus

1  2 1  1 1
Ln  2 − + 2  + - S(n) → 0 , or S(n) → Ln(2)
2  n n  2n 2

The convergence is very slow. (elementary techniques also show this result)

1 2 3 n
Example: S(n) = + + + +
4 4 4
1+ n 4+n 9+n n + n4
2

n −1 n
x 1 k
Hence ∫ dx → = lim ∑
0 x2 + n4 2 n →∞
k =1 k2 + n4

_______________________________________________________

Theorem 5.5 : Let S(n) = a1 (n) + a 2 (n) +  + a n (n) , and suppose there exists a non-
negative, bounded, and differentiable function f(x,t) defined for x ≥ 0 and t ≥ x , with
f (k, n) = a k (n) . Define φ(x) = f (x, x). Suppose
f x (x, t) < 0 , f t (x, t) < 0 , and φ(x) → 0 as x → ∞, and f(1,t) → 0 as t → ∞
Then
n
0 ← a n (n) ≤ S(n) − ∫ f (x, n)dx
1
≤ a1 (n) → 0 as n becomes infinite.

_________________________________________________________

## Proof: Draw a picture! ||

Example:
n n n
S(n) = 2 2
+ 2 2
+ ... + 2
1 +n 2 +n n + n2
π
The conditions of Theorem 4 are satisfied, giving lim S(n) = .
n →∞ 4
(elementary techniques also show this result).

## Tannery series a1 (n) + a 2 (n) +  + a n (n) are much more interesting if

a k (n) → 0 as n → ∞ for each k and Tannery's Theorem – the original version – does
not apply. If , in the Tannery Series S(n) = a1 (n) + a 2 (n) +  + a n (n) , each
a k (n) = a k , then S(n) is merely a normal series and consequently its absolute
convergence implies normal convergence. But if this is not the case , and each term
involves n, then absolute convergence does not imply convergence, as seen in the
following simple example.

k 
 n 2 if n even  1
Example: Set a k (n) =   . Then, for n even S(n) → , but for
-k 2
 2 if n odd 
n 
1
n odd S(n) → − , although the series converges absolutely to the value ½. Here
2
a k (n) → 0 as n → ∞ for each k . Observe that were the original Tannery Theorem
applicable, we would have a very uninteresting S(n) → 0 . However, the absolute
convergence of S(n) does imply the existence of at least one subsequence {n } with
j

{S } converging, since
nj S(n) ≤ a1 (n) +  + a n (n) ≤ M .

Analytic Functions . . .

__________________________________________________________

Theorem 5.6 : Define Fn (z) = a1,n (z) + a 2,n (z) +  + a n,n (z) where each term in the
Tannery series is analytic on D=(|z|<1) and there exists a positive M such that
M
a k,n (z) ≤ for each k ≤ n . Furthermore, assume there exists an interval (a,b) in
n
(-1,1) so that for each x in this interval, Fn (x) → λ (x) . Then Fn (z) → λ (z) , analytic
on D, uniformly on compact subsets of D.
___________________________________________________________
Proof: Follows immediately from the Stieltjes-Vitali Theorem , with Fn (z) < M . The
domain D may of course be generalized. ||

1
Corollary: Set a k,n (z) = Φ k,n (z) where each Φ k,n is analytic on D and Φ k,n (z) < M .
n
Then Fn (z) → λ (z) , analytic on D, uniformly on compact subsets of D.

1 1+nz 1 n n+ z
Example: Define Fn (z) = e +  + e with D=(|z|<1). It is easily shown that
n n
10
a k,n (z) < so that Fn (z) < 10.
n

## Let z = u + iv with 0<u<1, for example.

1 x+u
Writing f (x, t) = e t : f x ≥ 0 , f t < 0 , f(x,x) → 0 and f(1,t) → 0 , so that Theorem 8
t
1 x+u
n
applies , with lim Sn (u) = lim ∫ e n dx = e − 1 . Therefore, Fn (z) → λ (z) = e – 1.
n →∞ n →∞ n
1

## Inner & Outer Composition in a compact set – Convergence to analytic functions

______________________________________________________________

Theorem 5.7 : Let D=(|z|<1) and S be a simply-connected domain. Suppose there exists
a sequence of functions {f k,n (ζ, z)}k ≤ n analytic on both D and S, with
f k,n (S, D) ⊂ Ω , compact, ⊂ D . Suppose f k,n → f k uniformly on S × D as n → ∞ .
F (ζ, z) = f (ζ, z) , F (ζ, z) = F (ζ, f (ζ, z)) and
Set (1) F1 (ζ, z) =1f (ζ, z) n, F (ζ, z)n=−1 F n (ζ, f (ζ, z))
1,n 1,n p,n p −1,n p,n

## G (ζ, z) = f (ζ, z) , G (ζ, z) = f (ζ, G (ζ, z)) and

(2) G1 (ζ, z) =1f (ζ, z) ,nG (ζ, z)n= f (nζ−1, G
1,n 1,n p,n p,n p −1,n (ζ , z))

n →∞ n →∞

## (2) lim G n,n (ζ, z) = α (ζ ) = lim α k (ζ ) , where α k (ζ ) = f k (ζ, α k (ζ )) ,

n →∞ k →∞
analytic on S.
_________________________________________________________________
Proof: The previously cited Lorentzen Theorem and its extension by Gill, and Theorem
3.3 . The Stieltjes-Vitali Theorem  confirms the analyticity of the limit functions. ||

## Example: Tannery Continued Fraction

ζ
Set f k,n (ζ, z) = , where C ≥ 3, 0 ≤ δ(k,n) ≤ 1, lim δ(k,n)=0
C + δ(k, n) + z n →∞

1
Let S = D = (| z |< 1) and Ω = (| z |≤ 34 ) . Thus f k,n − f k < δ(k, n) ⋅ .
(C − 1) 2
ζ ζ ζ
Then Fn,n (ζ, z) =  and
C + δ(1, n) + C + δ(2, n) + + C + δ(n, n) + z
ζ ζ
lim Fn,n (ζ, z) =
n →∞ C + C +
= α (ζ ) =
1
2
(C 2 + 4ζ − C . )

## Constructing Tannery Series from analytic functions . . .

___________________________________________________________

Theorem 5.8 : Let f be a function analytic on D = (|z|<1), with f(0) = 0 , and |f(z)|<R.
Let α = α(k, n) and β=β(k,n) , k ≤ n, be real and imaginary parts of points within D.
n n n
If ∑ α + ∑ β ≤ M for all n, then
k =1 k =1
S(n) = ∑ f (α(k, n) + iβ(k, n))
k =1
≤ MR and there

## exists at least one subsequence {n j} such that {S(n j )} converges.

____________________________________________________________

## Of possible value is the following

n n
Corollary: Suppose ∑ α + ∑ β → 0 as n → ∞ . Then, for any function f defined as
k =1 k =1
n
above, ∑ f (α(k, n) + iβ(k, n))
k =1
→ 0 as n → ∞ .

## Here's an easy application:

ez − z − 1
Exercise: Use the function f (z) = in the corollary above
z
1 1 1
to prove that S(n) = (e − 1) + 2(e
n 2n
− 1) +  + n(e n ⋅n
− 1) → 1 .

## Evaluation of Tannery Series Not Satisfying Tannery’s Theorem

n ∞
Consider S n = ∑ ak (n) with ak (n) → ak but lim S n ≠ ∑ ak .
n →∞
k =1 k =1
The simplest interesting example of such a convergent TS is

1
n
1 k
φn = ∑ φ   → ∫ φ ( x)dx .
k =1 n  n  0

## Suppose one wishes to evaluate

n
kn + k 2 + n 2 + 1 n 1 kn + k 2 + n 2 + 1
ψn = ∑ = ∑ ψ ( k , n ) , ψ ( k , n ) = .
k =1 n( n 2 + k ) k =1 n n2 + k
2

Then
( k ) + ( k n ) + 1 + 1n ≈ φ  k 
ψ ( k , n) = n
2
where φ (x) = x 2 + x + 1 , and one might
 
1 + ( k n ) ⋅ 1n n
11
suspect that ψ n → . Indeed, this is the case, as is seen in the following simple
6
theorem:

_______________________________________________________________________
1 n
Theorem 5.9 : Given ψ n = ∑ψ (k , n) ,
n k =1
suppose there exists an integrable function φ ( x) with

1
k
I = ∫ φ ( x)dx and ∆ ( k , n) = φ   −ψ ( k , n) ≤ ε n ⋅ R , ε n → 0 .
0 n

Then limψ n = I .
n →∞
________________________________________________________________________

R
Proof: φn − ψ n ≤ ε n ⋅ n ⋅ →0 ||
n
Example: ψ n = ∑
n Sin ( )
k 2 +k
n 2 +1 k2 k2 + k
. Thus ∆(k , n) = Cos (ηk ,n ) ⋅ 2 − 2
1
≤ ≤ ⋅2 .
k =1 n n n +1 n
1
Hence limψ n = ∫ Sin( x 2 )dx .
n →∞
0

Here’s a curiosity couched as a problem: Partition the interval [0,1] into uneven,
increasingly lengthy subintervals, going from 0 to 1, to obtain
2 2
1 n n
2k 3 ( k + 1) + 2kn 2 ( n + 1)
∫ (x
2
+ 1)dx = lim ∑ Tn = lim ∑ 3
. Then manipulate Tn so as to
0
n →∞
k =1
n →∞
k =1 n3 ( n + 1)
n 1
obtain lim ∑ Tn = ∫ ( 2 x5 + 2 x )dx !
n →∞
k =1 0

References:

 J. Tannery, Introduction a la Theorie des Fonctions d'une Variable, Sec.183, 1886
 T. Bromwich, Introduction to the Theory of Infinite Series, 2nd Ed, 1926
 P. Henrici, Applied & Computational Complex Analysis, Vol. 1, 1974
 J. Gill, Compositions of Analytic Functions of the Form Fn(z) = Fn-1(fn(z)) , Lim fn(z)=f(z), J.
Comp. & Appl. Math. 23 (1988) 179-184
 L. Lorentzen, Compositions of Contractions, J. Comp. & Appl. Math. 32 (1990) 169-178
 J. Gill, Limit Periodic Iteration, Appl. Numer. Math. 4 (1988)297-308
 J. Gill, The Use of the Sequence Fn (z) = f n    f1 (z) in Computing Fixed Points of Continued
Fractions, Products, and Series, Appl. Numer. Math. 8 (1991) 469-4
 J. Gill, A Tannery Transformation of Continued Fractions and Other Expansions, Comm. Anal. Th.
Cont. Fraction Vol. 1, (1992)
 R. Remmert, Classical topics in complex function theory, Vol. 172, Springer (1998)
 S. Kojima, Convergence of Infinite Compositions of Entire Functions, arXiv:1009.2833v1]
 J. Gill, Convergence of Infinite Comp. of Anal. Functions, www.johngill.net (2010)